THE LEGAL POLITICS OF THE FORMATION OF JOB CREATION LAW WITHIN THE FRAMEWORK OF RESPONSIVE LAWS - Febriana, Lega Rahayu; Setiadi , Wicipto; Ahsin Thohari, Ahmad (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The introduction of the omnibus methodology to Indonesian lawmaking through the Job Creation Law has generated intense scholarly debate over the balance between regulatory efficiency and democratic legitimacy. Drawing on Nonet and Selznick’s responsive law theory, this study examines the legal politics underpinning the formation of Law No. 11 of 2020, PERPPU No. 2 of 2022, and Law No. 6 of 2023 within Indonesia’s civil‐law framework. Using normative legal research methods including statutory interpretation, constitutional doctrinal analysis, and comparative legal study this article traces the procedural trajectory from initial draft to successive judicial reviews (Decision Nos. 91/PUU-XVIII/2020 and 168/PUU-XXI/2023). The findings reveal systemic procedural deficiencies: exclusion of affected stakeholders, lack of meaningful public participation, and executive reliance on emergency powers instead of mandated legislative revision. The Constitutional Court’s interventions have served as corrective “strange attractors,” introducing “meaningful participation” requirements (right to be heard, right to be considered, and right to explanation) and compelling the government to adopt legislative reforms. However, persistent executive resistance underscores enduring tensions between efficiency‐oriented omnibus reforms and procedural legitimacy. The study concludes that forthcoming legislative efforts particularly the mandated separate Employment Law will determine whether Indonesia’s legal system advances toward genuinely responsive law or reverts to repressive practices. These insights hold broader significance for comparative constitutionalism and the global discourse on omnibus legislation in developing democracies.